Isolation, diagnosis of bacteria Xanthomonas axonopodis causing bacterial canker disease on citrus and resistance using antibiotics - Zahra ِAlmashhadany (مجلة التربية والعلم, 2019)
The study aimed at the determination of the pathogen of bacterial canker disease on citrus trees. The study showed that Xanthomonas axonopodis pv. citri was the major cause of the disease. The isolation process were carried by isolating 50 affected isolates obtained from various citrus fruit such as orange, lemon and tarring as well as some leaves and branches. For diagnosis, Morphological and biochemical tests were conducted. The sensitivity of these isolates was tested for six types of antibiotics; Azithromycin, Cefixime, Cefotaxime, Gentamycin, Streptomycin and Tetracycline. It was seen that all isolated bacteria were sensitive to all antibiotics. Cephotaxime showed the highest bacterial inhibition value 25mm, while Azithromycin showed the lowest one 11mm. The extract of 5 plants was also tested; onion, garlic, radish, grapes, and red pepper. Most of the used extracts affected the bacteria. The water extracted of the red pepper showed the highest inhibition value (10 mm) while the extracted water of grapes showed no inhibition value.